(3GdGSJPcGQ aj TQM ePGgH YdeGA GdCeUGQs - (3jhSa Hf YHO Gddg Hf YHO GdHQ GdfeQj GdbQWHj GdeGdcj, GHf YHO GdHQ , CHh YeQ , J (B463 (3g` s
(3ChdgG (B:s
(3HGH Gdfgi Yf Cf jSGaQ HGdbQBf Edi CQV GdYOh s
(3BNQgG (B:s
(3bGd CMeO Hf RgjQ bGd SeYJ eUYH Hf YHO Gddg GdRHjQi jbhd de jcf s
(3GdfSNI HgG MhGTs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B8 - (3U (B240 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B13 - (3U (B315s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
(3GdfSNI HgG JdhjK s
Keywords: (3GdMOjK h GdeUWdMs